Translation, transformation and refiguration: The significance of Jingdezhen and the materiality of porcelain in the work of two contemporary Chinese artists1. (1st September 2019) - Guest, Luise
AbstractIn December 2016 a group of researchers led by Professor Jiang Jiehong travelled to Jingdezhen as fieldwork for the Everyday Legend research project, funded by the Leverhulme Trust. Representing the White Rabbit Collection of Contemporary Chinese Art, Australia, I was invited to participate. This article developed from reflections on the fieldwork component of the research project, as well as the formal and informal discussions that took place, at the time and subsequently, in Shanghai, Birmingham, Groningen and London. In 2018, as a further development of this process of reflection, I conducted semi-structured interviews with two artists of different generations: the article examines how Liu Jianhua and Geng Xue approach the use of porcelain as a contemporary art material. Each has spent extensive periods of time in Jingdezhen and each is immersed in this particularly Chinese tradition. At the same time, each is identified (and identifies themselves) as practising in a global contemporary art context and participates in exhibitions and exchanges internationally. Considered in the context of current and historical discourses around global contemporaneity2 and its manifestations in twenty-first-century China, their work illuminates the key question that the Everyday Legend project was designed to examine: how can contemporary art and traditional Chinese craft practices intersect, informing and enriching each other? As representatives, respectively, of the generation who emerged into the first years of the post-Cultural Revolution Reform and Opening period, and of a younger generation educated partly outside China, they reveal how Chinese artists strategically negotiate local and global in positioning their work as contemporary reinventions of traditional forms and materiality.